KONSEP PENDIDIKAN ISLAM DALAM PRESPEKTIF KH. HAMIM DJAZULI (GUS MIEK) - M Muizzuddin; Khoirun Ni’am (JP : JURNAL PENDIDIKAN, 2019)
This study aims to uncover the concept of Islamic education according to K.H. Hamim Djazuli (Gus Miek) and discussed the relevance of the concept of K.H. Hamim Djazuli in facing the development of Science and Technology Progress with Islamic education. This research is library research by designing with a biographical and descriptive approach. The purpose of Gus Miek's Islamic education and Islamic education curriculum is very focused on the formation of character and personality of students as the most basic foundation in educational activities. So that not only makes humans have abilities in cognitive, affective, and psychomotor, but also embedded in the character and person who is a pious and virtuous person.Keywords: Concept of Education, Educational Psychology, Islamic Education